2020
DOI: 10.1088/1361-6382/ab8be7
|View full text |Cite
|
Sign up to set email alerts
|

Collins in Wonderland

Abstract: This paper is a continuation of our previous work on Bianchi cosmologies with a p-form field (where p ∈ {1, 3}) -or equivalently: an inhomogeneous, massless scalar gauge field with a homogeneous gradient. In this work we investigate such matter sector in General Relativity, and restrict to space-times of the particular Bianchi types VI 0 and VI h for h = −1/9 ∪ −1. Relying on our previous analysis, the aim of this paper is clean cut: We show that the versions of Wonderland found in B(VII 0 ) and B(VII h ) are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…[12,14]), other matter models (e.g. [19,29] and references therein), and finally the collisionless kinetic gas which is the subject of the present work. On the observational level, however, it has been shown that Planck data do not favour the inclusion of a Bianchi type VII h component [24], although the observed large-scale intensity pattern mimics only that of the Bianchi type VII h because the Bianchi type VII h is the most general SH spacetime that contains flat and open FLRW models for h = 0 and h = 0, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[12,14]), other matter models (e.g. [19,29] and references therein), and finally the collisionless kinetic gas which is the subject of the present work. On the observational level, however, it has been shown that Planck data do not favour the inclusion of a Bianchi type VII h component [24], although the observed large-scale intensity pattern mimics only that of the Bianchi type VII h because the Bianchi type VII h is the most general SH spacetime that contains flat and open FLRW models for h = 0 and h = 0, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To understand whether or not these principles are enforced by observational data, it is necessary to consider models that break at least some of them, and to test its observational consequences. To this end, a natural framework is provided by Bianchi models, which are spatially homogeneous cosmological models that may break three-dimensional (3D) rotational invariance in various ways: the fundamental congruence may possess shear [16][17][18][19][20][21] and vorticity [16,17,[22][23][24][25]; the matter sector may possess anisotropic stress [26][27][28][29][30][31][32][33][34][35][36][37][38] and tilt [39][40][41]; spatial sections of homogeneity may possess anisotropic curvature [19][20][21]42]. Note that the various types of anisotropies do not evolve independently but are intimately connected via Einstein's field equations.…”
Section: Introductionmentioning
confidence: 99%
“…[12,14]), other matter models (e.g. [19,29] and references therein), and finally the collisionless kinetic gas which is the subject of the present work. On the observational level, however, it has been shown that Planck data do not favour the inclusion of a Bianchi type VII h component [24].…”
Section: Introductionmentioning
confidence: 99%